O pensamento antropológico de Emílio Willems na história intelectual do Brasil - Golke, Marlete (2016)
In 1940, Emílio Willems published Assimilação e Populações Marginais no Brasil. In this period, tentatives to legitimate a national scenario and senses of seeking a brasility outlined the direction of intellectuality of the country. In this sense, we aim, with the referred work, to understand how it configured the thinking of Willems to comprehend the immigrant German and descendents in the perspective of the processes of assimilation and marginalization. For this, we divided the Dissertation in three chapters. In the first, we tried to present two contexts that become understandable the work of the author. In the contexts of debate about the main culturalists theories developed in the late of the centuries 19th and in the beginning of the century 20th, as well as the brasilian political-cultural context that launched the question of national identity as a problem to be defined. In the second chapter, we choose to analyzed the internal principles of the work of Willems, especially in the perspective of intentionality of the author exploiting some aspects that conducted the work Assimilação e Populações Marginais no Brasil. In a way that we can call the attention to the main concepts that willems used to construct his theory of assimilation. The last chapter is an analysis, in which aims at the conditions of intelligibility of the work to which refers the thought of Willems in the comprehension of the Teuto-Brazilian . We point to the understanding of his theory to think the idea of the foreign (immigrant teuto-Brazilian) like the one that comes from a theory and experience known for the comfort as another sphere that is strange to it for many reasons (economical, political, social and, especially, cultural). The process of marginalization of the immigrant is thought in this border of identity in whichis linked the Teuto-Brazilian in space and time. The concept Teuto-Brazilian is explored in its relation of hyphenation configuring the place and non-place of the foreign in the society that is going to occupy. This dissertation was developed in the Research Line Politics, Boarder and Society , in the Program of Post Graduation in History from Universidade Federal de Santa Maria, with the financial support of CAPES/DS.